2003
DOI: 10.1046/j.1471-4159.2003.02182.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially regulated transcripts in mouse striatum following methamphetamine treatment – an oligonucleotide microarray approach

Abstract: Methamphetamine is an addictive drug of abuse that can produce neurotoxic effects in dopamine nerve endings of the striatum. The purpose of this study was to identify new genes that may play a role in the highly complex cascade of events associated with methamphetamine intoxication. Using Affymetrix oligonucleotide arrays, 12 488 genes were simultaneously interrogated and there were 152 whose expression levels were changed following methamphetamine treatment. The genes are grouped into broad functional categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
82
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 63 publications
11
82
0
Order By: Relevance
“…COX-2 expression continued to increase up to 48 h after treatment, reaching a peak of 390% of control at 24 h. The levels of COX-1 protein were not changed by METH over the same time course. These results are in good agreement with our previous finding that COX-2 gene expression is increased by METH, whereas COX-1 gene expression remains unchanged (Thomas et al, 2004a). Using the time point of peak expression (24 h), we examined COX-2 protein levels in the wildtype littermates of COX-1 and COX-2 knockout mice (Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…COX-2 expression continued to increase up to 48 h after treatment, reaching a peak of 390% of control at 24 h. The levels of COX-1 protein were not changed by METH over the same time course. These results are in good agreement with our previous finding that COX-2 gene expression is increased by METH, whereas COX-1 gene expression remains unchanged (Thomas et al, 2004a). Using the time point of peak expression (24 h), we examined COX-2 protein levels in the wildtype littermates of COX-1 and COX-2 knockout mice (Fig.…”
Section: Resultssupporting
confidence: 90%
“…This situation is somewhat surprising in view of the larger role of the prostanoids in mediating other forms of neuronal injury, inflammation, and degeneration (Hurley et al, 2002). A comprehensive analysis of gene expression changes provoked by a neurotoxic regimen of METH substantiated these earlier findings by showing a drug-induced increase in expression of the genes for COX-2 and C/EBP (Thomas et al, 2004a). These initial gene expression results are extended presently by the demonstration that METH intoxication induces the expression of COX-2 protein.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They are expressed at constitutively low levels in microglia, and induced by inflammatory mediators (Mennicken et al, 1999;Färber and Kettenmann, 2005). Moreover, microglial cells are known to response to drugs of abuse, such as MRP and METH (Guilarte et al, 2003;Thomas et al, 2004;Khurdayan et al, 2004). In the present study, treatment with METH caused a morphological change in purified microglia, whereas MRP had no such effect.…”
Section: Discussionmentioning
confidence: 38%
“…In addition to these animal studies of sprouting in the striatum, several studies have demonstrated pronounced effects on microglial activation in methamphetamineexposed rodents (31,32), both in the striatum and, specifically, in the somatosensory cortex; these studies have suggested a role for microglial activation in methamphetamine neurotoxicity. Microglial activation has also been linked to astrocytosis (33), and both astrocytosis and depletion of glutamate-staining neurons have been observed in the somatosensory cortex of methamphetamine-exposed animals (34).…”
Section: Methamphetamine Effectsmentioning
confidence: 99%